Parametric cost analysis and quantitative risk assessment for developing strategies to counter risks in the design and production of medical aircraft in the Russian federation - George, Yuvaraj (International Journal of Engineering and Technology, 2021)
The objective is to identify potential risks in the aircraft development and to quantify the risks in the process, ultimately to find mitigating strategies. Monte-Carlo simulation for quantitative risk assessment and RAND DAPCA IV to calculate the cost are employed. These results are comprehended and collectively assessed with few assumptions. The assumptions are in due consideration to the local conditions, and thus they reflect in the approximations. These assumptions indicate the impact of the industrial and academic environment of the Russian Federation on the developmental cycle of the aircraft. The estimated financial risk for the development of an air medical ambulance for the Russian Federation is 29%, and the cost for unit production of the medical aircraft is nearly 19 million USD. The suggested strategies can reduce the financial risk to 22% and the cost for unit production of the medical aircraft to nearly 13 million USD.